2006
DOI: 10.1182/blood-2005-10-4239
|View full text |Cite
|
Sign up to set email alerts
|

Significance of circulating T-cell clones in Sézary syndrome

Abstract: Identification of malignant Sé zary cells by T-cell receptor (TCR) clonality studies is routinely used for the diagnosis of Sé zary syndrome, but T-cell clones expressed in a single patient have never been accurately characterized. We previously reported that CD158k expression delineates Sé zary syndrome malignant cells, and, more recently, we identified vimentin at the surface membranes of Sé zary cells and normal activated lymphocytes. In the present study, T-cell clones from 13 patients with Sé zary syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 48 publications
4
48
1
3
Order By: Relevance
“…KIR3DL2 may be because only about half of the expanded T-cell clones express CD158k and that CD158k expression is heterogeneous even within the malignant clones (31). Taking together, our data provide evidence for the down-regulation of several cytotoxicity-associated genes in Sezary syndrome.…”
Section: Discussionsupporting
confidence: 52%
“…KIR3DL2 may be because only about half of the expanded T-cell clones express CD158k and that CD158k expression is heterogeneous even within the malignant clones (31). Taking together, our data provide evidence for the down-regulation of several cytotoxicity-associated genes in Sezary syndrome.…”
Section: Discussionsupporting
confidence: 52%
“…These findings agree with earlier observations that loss or dim expression of CD7 and CD26 can be found in patients with benign inflammatory dermatoses 17,34,35 and other reactive conditions, 14 and aberrant dim CD3 can be observed non-neoplastic T cells. 29 Similarly, T-cell receptor gene rearrangements have been detected in samples of patients without clinical or histologic evidence of lymphoma or evidence of T-cell clonality shown by other methods. In this study group, Vb flow cytometric clonality assessment correlated with PCR testing for T-cell receptor gene rearrangements in 86% of cases, but flow cytometric Vb analysis had 100% specificity vs 77% for PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, several studies validated and expanded the use of flow cytometry to assess T-cell receptor Vb in T-cell malignancies. 13,25,[27][28][29][30] Morice et al 30 studied 29 T-cell lymphoproliferative disorders by flow cytometric Vb analysis, including 10 cases of cutaneous T-cell lymphoma, and showed a good correlation with molecular methods. This group expanded their study to include 11 Sézary syndrome and 6 mycosis fungoides cases, and showed that Vb analysis by flow cytometry was helpful for assessing clonality and quantifying the peripheral blood tumor burden.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Besides PLS3, several other molecular SS-restricted markers, including the transcription factor Twist, 6 have been identified by gene expression analysis on whole peripheral blood mononuclear cells. We also previously reported SS malignant cells characterization by their membrane expression of CD158k/ KIR3DL2 [7][8][9] and CD335/NKp46. 10 Here we investigated whether PLS3, Twist, KIR3DL2, and NKp46 gene expression profiling by quantitative PCR (qRT-PCR) can be used for an efficient molecular SS diagnosis.…”
mentioning
confidence: 99%